Inflammatory cytokine upd3 induces axon length–dependent synapse removal by glia - Federico Marcello Tenedini; Chang Yin; Jessica M. Huang; Neena Dhiman; Peter Soba; Jay Z. Parrish (Proceedings of the National Academy of Sciences, 2025)
Many neurodegenerative disorders (NDDs) preferentially affect neurons with long or complex axonal arbors but the cellular and molecular bases for neurite length-dependent vulnerability of neurons to degeneration is largely unknown. Using Drosophila sensory neurons as a model system we show that neuronal activation of the integrated stress response triggers expression of the Interleukin-6 homolog unpaired 3 ( upd3 ), which is both necessary and sufficient for axon length–dependent degeneration of presynapses. Upd3 activates phagocytic glia, triggering phagocytic removal of presynapses preferentially on neurons with long axons, thus revealing an intrinsic axon length–dependent vulnerability to glial insult. Finally, we found that axon length–dependent presynapse loss in fly models of human NDDs utilized this pathway, requiring upd3 and glial expression of the phagocytic receptor draper. Our studies identify inflammatory cytokine signaling and glial phagocytosis as key determinants of axon length–dependent vulnerability, thus mechanistically linking these hallmarks of NDDs.